Normal head and neck lymph nodes in the paediatric population. Issue 4 (April 2021) - Alves Rosa, J.; Calle-Toro, J.S.; Kidd, M.; Andronikou, S.
Abstract : AIM: To determine the normal range of head and neck lymph nodes in a paediatric population. MATERIALS AND METHODS: A retrospective review was undertaken of 200 brain magnetic resonance imaging (MRI) examinations in patients aged between 5 months to 16 years. Exclusion criteria included possible causes for lymphadenopathy. Studies were reported previously as normal. Eight regions were assessed for the presence of nodes, short and long axis of the largest node measured, and the ratio was calculated. RESULTS: Most commonly identifiable nodes were the deep cervical, submandibular, and posterior cervical in 100%, 99.5%, and 92.5% of studies. In the long axis, the three largest were the submandibular, deep, and posterior cervical with mean values of 19.7, 18.1, and 15.4 mm, respectively. For the S/L ratio, the three with the most oval shape were the pre-auricular, occipital, and submental with ratios of 0.64, 0.63, and 0.6, respectively. A positive correlation between the occipital and deep cervical lymph node groups with age was found to be stronger than the rest of localisations. CONCLUSION: This study characterises the normal distribution, size, and shape of head and neck lymph nodes in a healthy paediatric population, demonstrating that rounder and larger lymph nodes may be a normal finding, depending on their location and patient age. Highlights: Submandibular, Deep and Posterior cervical are the most common identifiable nodes. Submandibular, Deep, and Posterior cervical nodes are the largest. Preauricular, Occipital, and Submental nodes are the most oval-shaped. Correlation exists between age and node size (occipital and deep cervical groups). Rounder and larger lymph nodes may be a normal finding.